AUGMENTED REALITY BOOK PENGENALAN TATA LETAK BANGUNAN BESERTA LANDSCAPE ALAM PURA LUHUR BATUKARU - Made Bunga Anindya; Padma Nyoman Crisnapati; I Made Gede Sunarya; Made Windu Antara Kesiman (Universitas Pendidikan Ganesha, 2014)
This research aims to develop an application that is used as a means to introduce Pura Luhur Batukaru to the local and international community, so as to attract them to know, learn, and even preserving Pura Luhur Batukaru.This research includes research and development methods. In developing these applications using the waterfall model to the system testing phase. This application uses libraries vuforia capable of displaying three-dimensional objects into a temple building a real environment with the help of books and Android smartphones. Mechanical testing of theseapplications is done by giving questionnaires to the respondents. Questionnaire was used to test the spesific object with marker, test how long the objects showing in outside and indoors, and test the suitability of applications on several different Android smartphones.The results of this research in the form of a book containing information and images markers (markers) associated Pura Luhur Batukaru well as Augmented Reality Book-based application that is capable of displaying android Pura Luhur Batukaru building objects in the form of 3 dimensional image just above the marker (marker) complete with sound narrative explanations in English. This application can be used as a medium to maintain, introduce, at the same time preserving the nation's cultural assets.